Identification and Classification of Anthropogenic Landform in Parangtritis Hills Landscape - Dwi Putra, Boma Karunia; Setiawan, Muhammad Anggri; Mutaqin, Bachtiar Wahyu (Journal of Geography Science and Education, 2024)
Human activities alter the Earth's morphology into anthropogenic landforms, both in urban and rural areas, including Desa Parangtritis. These interventions create new characteristics in the landscape, such as pseudourban formations on plains and morphological changes in hills, posing environmental risks if not managed properly. This study uses a comparative descriptive spatial analysis method, comparing variations between anthropogenic and natural landforms. Digital Elevation Model (DEM) data and orthophoto were utilized to delineate and identify anthropogenic landforms. The results indicate that the hillsides in Desa Parangtritis are divided into structural and solutional landforms, each with varying levels of human intervention. The solutional landform falls under a "Slightly Modified Landscape" phase, while the structural landform has undergone significant anthropogenic intervention. Agrogenic land use dominates, with mixed gardens and fields as primary uses, while urbanogenic and traffic interventions are closely related to infrastructure development. The transformation of hills into anthropogenic landforms in Parangtritis reveals a strong human influence, not only forming pseudoterraces for agriculture but also altering land configuration through excavation and leveling, thus placing it in a "semi-natural landscape" phase. These interventions increase the risks of erosion and landslides and reduce infiltration capacity. The study demonstrates that landform changes due to anthropogenic intervention in the hills of Desa Parangtritis require careful conservation planning to protect the environment and minimize the negative impacts of human activities in the area.